Legal position of the issues associated with main contractor's insolvency [compact disc] - 241815 Ng, Sock Hooi (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2006